Ausgrabungstätigkeit in Syrien (3)
ersch. 1985; A. Mahmoud, Tall Aǧāǧa; P.E. Pecorella - M. Salvini, Tall Barri/Kaḫat; E. Strommenger, Tall Bi‘a; D. Oates, Tell Brak; H. Seeden, Buṣra eski-Šām; W. Orthmann, Tall Chuēra; E. Brümmer, Dmeir; G. van Driel, Ǧabal ’Arūda; M. Moussli, Ḥadata; W. Orthmann, Tall Halawa; M. van Loon, Tall Hammām et-Turkmān; J. Cauvin - O. Aurenche, Tall al-Kowm; H. Weiss, Tall Leilan; D. Machule, Tall Munbaqa; A. Schmidt-Colinet, Palmyra; P. Courbin, Rās al-Bassit; А. Воunni, Ras Ibn Hani; H. Kühne, Tall Šēḫ Ḥamad/Dūr-Katlimmu